2021
DOI: 10.3390/cells10113184
|View full text |Cite
|
Sign up to set email alerts
|

Bench Research Informed by GWAS Results

Abstract: Scientifically interesting as well as practically important phenotypes often belong to the realm of complex traits. To the extent that these traits are hereditary, they are usually ‘highly polygenic’. The study of such traits presents a challenge for researchers, as the complex genetic architecture of such traits makes it nearly impossible to utilise many of the usual methods of reverse genetics, which often focus on specific genes. In recent years, thousands of genome-wide association studies (GWAS) were unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 253 publications
(271 reference statements)
0
2
0
1
Order By: Relevance
“…20 In addition, the impact of genetic variation on the outcome is chronological, that is, Mendelian randomization can solve the problem of reverse causality (Figure 1). 21 With the rapid development of genome-wide association studies (GWAS) recently, 22 it is much more convenient to obtain the genetic associations with both exposure and outcome, especially in the two-sample MR setting.…”
Section: Introductionmentioning
confidence: 99%
“…20 In addition, the impact of genetic variation on the outcome is chronological, that is, Mendelian randomization can solve the problem of reverse causality (Figure 1). 21 With the rapid development of genome-wide association studies (GWAS) recently, 22 it is much more convenient to obtain the genetic associations with both exposure and outcome, especially in the two-sample MR setting.…”
Section: Introductionmentioning
confidence: 99%
“…Aun así, después habrá que realizar algunos análisis adicionales para confirmar que realmente es esta variante, y no otro SNP cercano que no haya sido estudiado, la que está relacionada con el rasgo (Uffelmann et al, 2021). Como ya se ha nombrado anteriormente, GWAS es actualmente la mejor técnica para detectar la adaptación local, además de ser una de las técnicas más utilizadas para los análisis genéticos que buscan relaciones entre genes y rasgos (Kondratyev et al, 2021). Sin embargo, esta técnica no es perfecta, y se ha topado con una dificultad en la detección que es difícil de superar, la identificación de marcas de selección sutiles en el genoma (Fu y Akey, 2013).…”
Section: Detección De Las Adaptaciones Localesunclassified
“…The complex genetic architecture of SZ includes common alleles, rare gene mutations, copy number variations, deletions, and chromosomal translocations. Genome-wide association studies (GWAS) have identified genetic variants associated with SZ [3] that have served as a comprehensive resource for further mechanistic studies [4]. GWAS [3,5,6] and recent genetic studies [7] linked a number of transcription factors (e.g., TCF4, PRDM14, POU5F1, TEAD1, ZEB2, FOXP1, ZNF804A, etc.…”
Section: Introductionmentioning
confidence: 99%